The option trader's workbook : a problem-solving approach - Augen, Jeffrey (FT Press, 2012)
Successful options trading requires extensive practice. Most options books offer theory and strategies, but don't offer the practice needed to prepare for real-world trades, where the wrong split-second decisions can cost you dearly. Expert trader Jeff Augen covers every key scenario you'll encounter in modern options trading, guides you through successful trade executions, and shows how to overcome key pitfalls that trip up most traders. You'll walk through trades designed to profit from changing prices and volatility, time decay, rapid price spikes, and many other factors. This second edition introduces powerful new techniques, and reflects the long-term impacts of the 2009 crash. New problems include: New CBOE Weekly Options Expiration options, and their unique pricing dynamics. Using collars, covered calls, and covered puts to structure income-generating trades with well-defined risk profiles. Using ratio trading, VIX options, volatility ETFs, and variance trading to generate profits from shifts in volatility. Each section contains beginner, intermediate, and advanced sections, helping you build your skills one trade at a time, no matter how much experience you have--or how little. You'll find several hundred questions, all designed to mirror real life, and supported with clearly explained solutions.